Heart Failure and Coronavirus Disease-19 - Hasan, Refli (Open Access Macedonian Journal of Medical Sciences, 2021)
Globally, 4.2% population suffer from heart failure. The condition has a mortality rate between 56% and 78%. Coronavirus disease-2019 (COVID-19) was first reported in December 2019 and became a pandemic since March 11, 2020. As COVID-19 emerges, cardiovascular disorders including, heart failure, become one of the most common comorbidity that increase the risk for contracting the disease. Heart failure and COVID-19 have reciprocal relationship. Patients with heart failure are at higher risk for COVID-19 with more unfavorable outcome. COVID-19 itself may deteriorate pre-existing heart failure in the subject. This situation is mediated by the presence of angiotensin converting enzyme-2 (ACE-2) in cardiac myocytes and pericytes, direct effect of viral invasion to myocytes and pericytes, downregulation of ACE-2 which hampers cardiovascular function, and uncontrolled inflammation known as cytokine storm. Prudent management, including implementation of telemedicine, continuation of ACE inhibitor and angiotensin receptor blocker, and medications’ side effects monitoring, is important in managing patients with coexisting heart failure and COVID-19.